2020
DOI: 10.1080/00940798.2020.1791724
|View full text |Cite
|
Sign up to set email alerts
|

Cultivating Supports while Venturing into Interviewing during COVID-19

Abstract: As the COVID-19 pandemic has magnified structural inequities worldwide, the field of oral history and its practitioners are reexamining established best practices. The pandemic has heightened awareness of underlying issues in oral history with the challenges of social distancing, financial collapse, privacy concerns in an increasingly virtual world, and the uneven impacts of the pandemic. This article calls for shoring up and expanding support structures when conducting interviews during and about the pandemic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 1 publication
0
5
0
Order By: Relevance
“…This enabled the research to comply with social distancing requirements, thus protecting the physical health of interviewers and interviewees. Virtual interviews also enabled participants to express any vulnerabilities, emotions and private experiences in their own safe and comfortable space [ 40 ]. Interviews lasted an average of 45 min (ranging from 23 min to 93 min).…”
Section: Methodsmentioning
confidence: 99%
“…This enabled the research to comply with social distancing requirements, thus protecting the physical health of interviewers and interviewees. Virtual interviews also enabled participants to express any vulnerabilities, emotions and private experiences in their own safe and comfortable space [ 40 ]. Interviews lasted an average of 45 min (ranging from 23 min to 93 min).…”
Section: Methodsmentioning
confidence: 99%
“…During the pandemic outbreak, the nurses' working environment was rife with stressful conditions. Hence, in order to reduce the strain and enable them to undergo the interviews in a comfortable and neutral place for them and reduce COVID-19 transmission risk for both parties [29], online interviews were done via Zoom™ [30] and were audioand video-recorded, with notes written by the interviewer. The online interviews were scheduled according to the nurses' times and technologies accessibilities in an attempt to listen to their views and perspectives regarding their experience of providing extensive care to COVID-19 patients.…”
Section: Participants and Proceduresmentioning
confidence: 99%
“…I was also cognizant of privacy and security concerns. I conducted the remote interviews from a room in my home with the door closed, and I encouraged narrators to pick days and times convenient for them so they would be comfortable in their own spaces in terms of who else may be in the household (Kaplan, 2020). From the very first interview, I found that even though none of my questions specifically addressed COVID-19, the narrators sometimes referred to the pandemic or compared and contrasted their quiltmaking experiences before and during the pandemic.…”
Section: Conducting Research During a Pandemicmentioning
confidence: 99%
“…From the very first interview, I found that even though none of my questions specifically addressed COVID-19, the narrators sometimes referred to the pandemic or compared and contrasted their quiltmaking experiences before and during the pandemic. I carefully looked and listened for non-verbal cues about any discomfort the narrator may have been feeling, and I moved on quickly if they seemed uncomfortable with a particular line of questioning because I understood they could be experiencing some level of pandemic-related mental or emotional exhaustion (Kaplan, 2020).…”
Section: Conducting Research During a Pandemicmentioning
confidence: 99%
See 1 more Smart Citation